Efficacy of Ovarian Artery Embolization for Uterine Fibroids. Issue 2 (May 2015) - Campbell, Jennifer; Rajan, Dheeraj K.; Kachura, John R.; Jaskolka, Jeffrey; Beecroft, J. Robert; Sniderman, Kenneth W.; Simons, Martin E.; Tan, Kong T.
Purpose: The objective of the study was to assess the efficacy of ovarian artery embolization (OAE) treatment for symptomatic uterine leiomyomas. Methods: A retrospective review of 17 patients who underwent OAE in conjunction with uterine artery embolization in a 6-year period (2006-2012) was performed. Ten patients had previous failed embolization, while 7 had not received any embolization therapy before. Percent uterine volume change, percent dominant fibroid volume change, and percent dominant fibroid infarction were assessed with magnetic resonance (MR) imaging. Resolution of menorrhagia, dysmenorrhea/pain, and bulk and/or pressure symptoms including urinary frequency were evaluated clinically. Change in menopausal state was also an outcome of interest. Results: Mean MR imaging follow-up was performed 3 months post-OAE. MR images showed complete infarction in the majority of cases (64.7%; n = 11), with infarction rates of 90%-100% in 3 cases, 1 case with 30%-50% infarction, and 2 cases with 0%-10% infarction. Average uterine size reduction on MR was 32.3% (95% confidence interval [CI]: 22.5%-42.2%; P < .001). The average size reduction for the dominant fibroid was 42.4% (95% CI: 27.7%-57.0%; P = .01). The mean time to final follow-up visit was 11 months. At this point complete symptom resolution (menorrhagia, dysmenorrhea and bulk-related) was achieved in 82.4% (n = 14) of cases. At the final follow-up 11.8% (n = 2) of cases reported menopause. Conclusions: We observed OAE to be an effective and safe adjunct to uterine artery embolization when hypertrophic ovarian artery(ies) require intervention. However, incomplete fibroid infarction of 23% remains a concern with a potential for long-term treatment failure. In addition, long-term effect on ovarian function is uncertain.